KEDELAI HITAM SEBAGAI BAHAN BAKU KECAP TINJAUAN VARIETAS DAN LAMA FERMENTASI TERHADAP MUTU KECAP (BLACK SOYA AS A RAW MATERIAL FOR SOYA THE STUDY OF VARITYS AND TIME OF FERMENTATION TO SOYAS QULITY) - Setiawati, Bernadetta Budi (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2006)
As a raw material of the fickle product, black soy has the constraint to appearantance of the product which is not appropriate with consumers appetite. As the result, products diversification from the raw material of black soy is very finite, cultivations result is less be accepted by market because of the lowering demand and the debility of cultivation will emergen finally. This research is intended to determine the eligibility of soyas making from black soy as a raw material evaluated from soyas quality from the time of fermentation and also this variety. The result of this research indicates that the time of fermentation for 4 weeks (30 days) and from UGM organic black soy variety yields the soyas quality with the highest value seen from nature of color, smell/aroma and sweets taste (very taken a fancy to / sweetest), and also mount the viscosity at second level. The researchs result of soyas making from black soy as a raw material show that the technical eligibility (raw material, process, product), quality eligibility (process) and financial eligibility (Benefit/Cost Ratio and rentability of bank price).